The Degree Of Study Of The Medical Thriller Genre In World Literary Criticism (Texas Journal of Philology, Culture and History, 2026)
The medical thriller, as a distinct sub-genre of suspense fiction, has undergone a significant transformation from a "pulp" category to a sophisticated subject of academic inquiry. This article evaluates the current degree of scholarly engagement with the medical thriller in global literary criticism. It examines the genre’s evolution from Gothic roots to modern bio-technological narratives. The study highlights the linguo-poetic features—such as the aesthetic use of medical jargon—and the conceptual frameworks that define the genre's structure. Furthermore, it identifies the lack of comparative research in Uzbek philology and suggests a roadmap for integrating global medical-thriller discourse into the national literary context.